Ion Beam Stimulation Therapy With a Nanoradiator as a Site-Specific Prodrug - Kim, Jong-Ki; Seo, Seung-Jun; Jeon, Jae-Geun (Frontiers in Physics, 2020)
Because Bragg-peak energy cannot be delivered individually to multiple scattered tumor infiltration or diffusive lesions, instead, energy of ion beam can be adjusted to traverse entire body for selective activation of the nanoparticles inside target lesions with the ion fluence comparable to Bragg peak. This Coulomb stimulation on nanoparticles generate low energy electrons (LEEs) and characteristic fluorescent X-ray (XFL) from the nanoparticle surface that effectively transform inert nanoparticles into a nanoradiator like conversion of prodrug into drug. In contrast, relatively small plateau dose absorbed on beam path ensure minimal effect on normal. This simple but innovative approach enable traversing ion beam therapy (TIBS) on either tumor infiltration or diffusive non-oncological lesions unprecedentedly. Theoretical background and unique efficacy of TIBS are demonstrated by several proof-of-concept studies with animal disease models and molecular-targeted high-Z NP.